Properties of AlN/GaN Heterostructures Grown at Low Growth Temperatures with Ammonia and Dimethylhydrazine - Caroline E. Reilly (MDPI AG, 2021)
The integration of different electronic materials systems together has gained increasing interest in recent years, with the III-nitrides being a favorable choice for a variety of electronic applications. To increase flexibility in integration options, growing nitrides material directly on semi-processed wafers would be advantageous, necessitating low temperature (LT) growth schemes. In this work, the growth of AlN and GaN was conducted via metalorganic chemical vapor deposition (MOCVD) using both NH3 and DMHy as N-precursors. The relationships between growth rate versus temperature were determined within the range of 300 to 550 °C. The growth of AlN/GaN heterostructures was also investigated herein, employing flow modulation epitaxy MOCVD at 550 °C. Subsequent samples were studied via atomic force microscopy, X-ray diffraction, TEM, and Hall measurements. Two-dimensional electron gases were found in samples where the LT AlN layer was grown with NH3, with one sample showing high electron mobility and sheet charge of 540 cm2/V∙s and 3.76 × 1013 cm−2, respectively. Inserting a LT GaN layer under the LT AlN layer caused the mobility and charge to marginally decrease while still maintaining sufficiently high values. This sets the groundwork towards use of LT nitrides MOCVD in future electronic devices integrating III-nitrides with other materials.